Investments in Painting: The interaction of monetary return and psychic income - Martin M.G. Fase (SUERF - The European Money and Finance Forum, 2001)
The financial press gives very regular attention to art and culture in their many forms. Business newspapers such as the Financial Times, the Wall Street Journal, Het Financieele Dagblad and De Financieel Economische Tijd give over plenty of space in their weekend editions to news of art auction prices and exhibitions of major or less well-known works. As well as this practical outlook, more theoretical economists have given increasing attention to the economics of art since the 1970s. There has been a remarkably large amount of research into the pricing of art and the closely associated subject of the return on purchases of art. This centres on painting in general and on individual painters. The attention to painting in the business press is without doubt prompted by the need for journalistic variety, plus the wish to impart a cultural element to the reporting. The provision of market information to readers is, of course, another significant motive. It is less simple to explain the academic interest of economists. At first sight, it seems exotic. But that is a hasty conclusion. Along with intellectual curiosity, there is probably a role for the need to apply trusted analytical methods to new areas of research. Whatever the reason, there is a place for the systematic study of the literature on the sense and nonsense of investing in painting and this is the objective of this paper. It is, however, also a report of explorations in a field that has fascinated me personally as an economist for many years.
Keywords: 330; Economics of art; Paintings as an investment; Art and psychic income; Cultural policy; Museum collections; Kapitalanlage; Kunstwerk